Effect of destabilisation and tempering heat treatments on hardness and corrosion behavior of 28 wt.%cr cast irons with mo addition - Amporn Wiengmoon (2018)
© 2018 Trans Tech Publications, Switzerland. The effects of destabilisation and tempering heat treatments on hardness and corrosion behavior in 28 wt.%Cr-2.6 wt.%C cast irons with up to 6 wt.%Mo addition were studied. The irons were destabilised at 1025o C for 4 h and air cooled. Tempering was carried out at 450o C for 4 h. Phase identification and microstructure were investigated by X-ray diffraction (XRD), light microscope (LM), scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). Vickers macro-hardness was measured. A potentiodynamic technique was used to indicate aqueous corrosion resistance. The results revealed that the as-cast microstructure of 28 wt.%Cr iron consisted of primary austenite dendrites with eutectic M7 C3 carbides. In the irons with 6 wt.%Mo addition, eutectic carbides including M7 C3, M23C6 and M6 C were found. After destabilisation, the microstructure contained secondary carbide precipitates within an essentially martensitic matrix. Vickers macro-hardness of the as-cast and destabilised irons increased from 500 HV30 and 736 HV30 in the 28 wt.%Cr iron up to 570 HV30 and 870 HV30 in the iron with 6 wt.%Mo addition. Tempering slightly increased the macro-hardness. The as-cast 28 wt.%Cr iron had the lowest values for critical current density and passive current density. The destabilised + tempered treatment gave the lowest corrosion resistance.